2020
DOI: 10.12697/akut.2020.26.02
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived coaching behaviours on sport performance among female aesthetic group gymnasts

Abstract: This study aimed to test the relations of perceived autonomy-supportive and controlling behaviours from coaches with athletes’ sport performance during competition in a context of female aesthetic group gymnastics. In line with self-determination theory, it was expected that the sequence of perceived psychological needs satisfaction and autonomous motivation, and psychological needs frustration and controlled motivation would mediate these relationships. Female aesthetic group gymnasts (n=128) ages 11–20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
4
8
0
Order By: Relevance
“…The results obtained in the structural equation modeling provided criterion validity evidence for the Romanian sport version of the NSFS. They are in line with the hypotheses proposed in this research and with previous research conducted in sport [17][18][19][20][21]. Particu-larly, need satisfaction positively predicted autonomous motivation, while need frustration positively predicted both controlled motivation and amotivation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained in the structural equation modeling provided criterion validity evidence for the Romanian sport version of the NSFS. They are in line with the hypotheses proposed in this research and with previous research conducted in sport [17][18][19][20][21]. Particu-larly, need satisfaction positively predicted autonomous motivation, while need frustration positively predicted both controlled motivation and amotivation.…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, we gathered criterion validity evidence by inspecting the predictive relationships of need satisfaction and need frustration on motivation. In accordance with research conducted on sport [17][18][19][20][21], we hypothesized that autonomy, competence, and relatedness satisfaction would positively predict autonomous motivation, while the frustration of each BPN would positively predict both controlled motivation and amotivation in professional athletes.…”
Section: The Present Researchmentioning
confidence: 62%
See 1 more Smart Citation
“…To the best of our knowledge, there are very few studies in the sport context that have examined the differentiated effects of both athletes' perceptions of need-supportive and controlling coaching style on reported need satisfaction, need frustration, motivation and sport commitment. 19,21,28,30,31 The results from these studies did not shed light on the cross-relationships between these variables. For instance, the studies by Bartholomew et al 28 and González et al 30 revealed that while the perceived autonomy-supportive style was negatively related to reported need frustration, a non-significant relationship was found between perceived controlling style and reported need satisfaction among athletes.…”
Section: The Present Studymentioning
confidence: 74%
“…In this regard, the SDT postulates that autonomous forms of motivation would lead to adaptive affective behavioral and cognitive outcomes ( Ryan & Deci, 2020 ; Ryan et al, 2021 ) such as performance ( Koka et al, 2020 ), commitment ( Pulido et al, 2018 ), intention to continue the sports practice ( Monteiro et al, 2018 ) and resilience ( Trigueros et al, 2020 ) among athletes. Particularly, from a theoretical viewpoint, the relationship between autonomous forms of motivation and resilience is argued in the fact that autonomously motivated athletes often tended to improve their skills and overcome challenges regardless of unfavorable and stressful events, promoting a resilient behavior ( Trigueros et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%